Human Papillomavirus Vaccination in Male and Female Adolescents Before and After Kidney Transplantation: A Pediatric Nephrology Research Consortium Study - Nailescu, Corina; Nelson, Raoul D.; Verghese, Priya S.; Twombley, Katherine E.; Chishti, Aftab S.; Mills, Michele; Mahan, John D.; Slaven, James E.; Shew, Marcia L. (Frontiers in Pediatrics, 2020)
Background: Kidney transplant (KT) recipients have higher incidence of malignancies, including Human Papillomavirus (HPV)-associated cancers. Thus, HPV vaccines may have an important role in preventing HPV-related disease in this population; however, immunogenicity and safety data are lacking. Objective: To examine the immunological response and tolerability to HPV vaccination in pediatric KT recipients compared to future KT candidates. Methods: The quadrivalent HPV vaccine was administered to girls and boys age 9 to 18 recruited from 7 centers part of the Pediatric Nephrology Research Consortium. Subjects were recruited for three groups: 1. CKD: chronic kidney disease stages 3, 4 and 5 not on dialysis; 2. Dialysis; 3. KT recipients. The outcome consisted of antibody concentrations against HPV 6, 11, 16 and 18. Geometric mean titers (GMTs) and seroconversion rates were compared. Vaccine tolerability was assessed. Results: 65 participants were recruited: 18 in the CKD, 18 in the dialysis and 29 into the KT groups. KT patients had significantly lower GMTs after vaccination for all serotypes. The percentages of subjects who reached seroconversion were overall lower for the KT group, reaching statistical significance for HPV 6, 11 and 18. Comparing immunosuppressed subjects (anyone taking immunosuppression medications, whether KT recipient or not) with the non-immunosuppressed participants, the former had significantly lower GMTs for all the HPV serotypes and lower seroconversion rates for HPV 6, 11 and 18. KT females had higher GMTs and seroconversion rates for certain serotypes. There were no adverse events in either group. Conclusions: HPV vaccine was well-tolerated in this population. Pediatric KT recipients had in general lower GMTs and seroconversion rates compared to their peers with CKD or on dialysis. Immunosuppression played a role in the lack of seroconversion. Our results emphasize the importance of advocating for HPV vaccination prior to KT and acknowledge its safety post transplantation. Future studies are needed to investigate the effect of a supplemental dose of HPV vaccine in KT recipients who do not seroconvert and to evaluate the long-term persistence of antibodies post-KT.